Stock Performance Analysis of Kompas 100 Before and After The Pandemic Covid-19 in Indonesia - Teguh Agus Setiawan; Siti Nur Haliza; Nur' Alvia Mulki; Suhadiono Suhadiono (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
AbstractThis study analyzes the performance of the Kompas 100 stock before and after the COVID-19 pandemic in Indonesia in the period 2019 – 2020. This study uses stock price data for 40 companies listed in the Kompas 100 stock group on the Indonesia Stock Exchange. Data were analyzed using IBM SPSS Version 25 with a paired sample difference test model (compare means paired samples t test). This study found that there were differences in the situation before and after the COVID-19 pandemic on the volatility of the Kompas 100 stock price on the Indonesia Stock Exchange. In general, there has been a decline in the share price of Kompas 100 on the Indonesia Stock Exchange which reached -12.46% after the pandemic in 2020 compared to before the COVID-19 pandemic situation in 2019.